Effect of laser pulse capacity on photonic crystal fiber properties at communication windows - Oday Amin (College of Education for Pure Sciences, 2012)
Abstract: In this paper we demonstrate the effect of laser pulse power on the main properties of the photonic crystal fibers (PCFs) that represented by refractive index, numerical aperture, effective area and dispersion. All these properties have been studied at the communication windows (0.8 µm, 1.31 µm, 1.55 µm). The results of this work show that, when the laser pulse power is increased, the refractive index and effective area increase while the numerical aperture decreases over the wavelength range of (0.5 µm-2 µm). Besides, the results reveal that there are an increase of the dispersion value at the communication windows (0.8 µm, 1.31 µm) and a decrease of the some value at the window (1.55 µm).